2018
DOI: 10.1186/s12885-017-3938-5
|View full text |Cite
|
Sign up to set email alerts
|

An oncogenic mutant of RHEB, RHEB Y35N, exhibits an altered interaction with BRAF resulting in cancer transformation

Abstract: BackgroundRHEB is a unique member of the RAS superfamily of small GTPases expressed in all tissues and conserved from yeast to humans. Early studies on RHEB indicated a possible RHEB-RAF interaction, but this has not been fully explored. Recent work on cancer genome databases has revealed a reoccurring mutation in RHEB at the Tyr35 position, and a recent study points to the oncogenic potential of this mutant that involves activation of RAF/MEK/ERK signaling. These developments prompted us to reassess the signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Rheb1's role in cancer is intricate, impacting cell growth and apoptosis, albeit the precise mechanisms remain unclear [160,182]. It influences apoptosis via mTORC1 and independently, particularly through its interaction with FKBP38, Bcl-2, and Bcl-XL [183].…”
Section: Effect Of Rheb1 On Resisting Cell Deathmentioning
confidence: 99%
“…Rheb1's role in cancer is intricate, impacting cell growth and apoptosis, albeit the precise mechanisms remain unclear [160,182]. It influences apoptosis via mTORC1 and independently, particularly through its interaction with FKBP38, Bcl-2, and Bcl-XL [183].…”
Section: Effect Of Rheb1 On Resisting Cell Deathmentioning
confidence: 99%
“…As the RB domains of the RAF paralogs are conserved (33), mainly regarding their RAS binding residues (Fig. S3 (61). They have shown that a variant of RHEB (Y35 to asparagine; Y32 in HRAS) impedes RHEB interaction with BRAF leading to an increased BRAF/CRAF heterodimerization and thus activation of the MAPK pathway.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…They have shown that a variant of RHEB (Y35 to asparagine; Y32 in HRAS) impedes RHEB interaction with BRAF leading to an increased BRAF/CRAF heterodimerization and thus activation of the MAPK pathway. Accordingly, they have proposed a dual function for RHEB, suppression of the MAPK pathway and mTORC1 activation (61).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Yield 36%, m.p. 240-242 (20) To a solution of 2-amino-5-chloronicotinamide 19 (34.97 mmol) in 1,4-dioxane (30 mL) was added diphosgene (111.90 mmol), then the mixture was charged with N 2 and stirred at 120 • C for 12 h. After completion (monitored by TLC), cooled to r.t. Dry diethyl ether (100 mL) was added and stirred at r.t for 1 h, the precipitation separated out. Suction and drying to give a brown solid.…”
Section: -Chloro-1h-pyrazolo[34-d]pyrimidine (9)mentioning
confidence: 99%
“…Phosphorylated PI3K could activate RAS via several mechanisms [18], thereby reactivating the ERK pathway. Meanwhile, inhibition of PDK1, AKT or Rheb could increase RAF activities [19][20][21]. Besides, the classic feedback loop (S6-IRS1-PI3K) leads to activation of PI3K but also ERK signaling [22].…”
Section: Introductionmentioning
confidence: 99%